2018
DOI: 10.1093/cid/ciy001
|View full text |Cite
|
Sign up to set email alerts
|

Are We on Our Way to Achieving the 2020 Goals for Schistosomiasis Morbidity Control Using Current World Health Organization Guidelines?

Abstract: BackgroundSchistosomiasis remains an endemic parasitic disease affecting millions of people around the world. The World Health Organization (WHO) has set goals of controlling morbidity to be reached by 2020, along with elimination as a public health problem in certain regions by 2025. Mathematical models of parasite transmission and treatment impact have been developed to assist in controlling the morbidity caused by schistosomiasis. These models can inform and guide implementation policy for mass drug adminis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
102
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(117 citation statements)
references
References 26 publications
6
102
1
3
Order By: Relevance
“…An alternative approach using deterministic compartment-based models, has been used to investigate the effects of vaccination, but this approach allows for less scope for including biological complexity [22, 23]. The transmission cycle, which is related to previously published models [11, 21, 24], is as follows:Mature adult schistosomes reproduce within human hosts monogamously. To account for within-host competition, fecundity (egg production per female schistosome) decays exponentially with the total number of mature schistosomes currently contained in the human host.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An alternative approach using deterministic compartment-based models, has been used to investigate the effects of vaccination, but this approach allows for less scope for including biological complexity [22, 23]. The transmission cycle, which is related to previously published models [11, 21, 24], is as follows:Mature adult schistosomes reproduce within human hosts monogamously. To account for within-host competition, fecundity (egg production per female schistosome) decays exponentially with the total number of mature schistosomes currently contained in the human host.…”
Section: Methodsmentioning
confidence: 99%
“…However, several recent studies in Africa have demonstrated limited progress in reducing prevalence in localized high-transmission areas, despite high MDA coverage [79]. Mathematical modelling suggests that high coverage of both children and adults over sustained periods of time is required for MDA to control schistosomiasis in high-transmission areas, which may prove to be beyond practical limits [10, 11]. …”
Section: Introductionmentioning
confidence: 99%
“…For both of these infections, current guidelines suggest that treatments should be targeted at children, with different frequencies according to prevalence. The modeling studies in this special issue suggest that the current guidelines might be altered slightly to optimize their impact, through either targeting adults or changing the thresholds for switching strategies [40,41] (Table 2).…”
Section: Mass Drug Administrationmentioning
confidence: 99%
“…All of the articles on MDA policies highlight the importance of the epidemiological setting, the appropriate group being targeted, and systematic nonadherence, where particular groups either do not have access to or are refusing treatment, and note that these are often poorly measured ( Figure 3) [40,41,[43][44][45]. The issue of systematic nonadherence has been highlighted in modeling studies for many years but has recently become a point of focus again [11,46,47].…”
Section: Mass Drug Administrationmentioning
confidence: 99%
“…As standard methods for diagnosing schistosomiasis are quite insensitive, experts believe that actual estimates of the number of people currently infected with schistosomiasis ranges between 400 and 600 million based on the hypothesis that there is a one to one (1:1) ratio between egg-positive infected individual and an egg-negative infected individual [3]. Schistosomiasis is estimated to cause 280,000 deaths annually in 78 countries and about 3.8 million disability adjusted life years credited to the disease [4,5].…”
Section: Introductionmentioning
confidence: 99%